Mechanisms of Normalisation of Bone Metabolism during Recovery from Hyperthyroidism: Potential Role for Sclerostin and Parathyroid Hormone - Elżbieta Skowrońska-Jóźwiak; Krzysztof C. Lewandowski; Zbigniew Adamczewski; Kinga Krawczyk-Rusiecka; Andrzej Lewiński (International Journal of Endocrinology)
Sclerostin, a protein expressed by osteocytes, is a negative regulator of bone formation. The aim of the study was to investigate the relationship between parathyroid hormone (PTH) and markers of bone metabolism and changes of sclerostin concentrations before and after treatment of hyperthyroidism. Patients and Methods. The study involved 33 patients (26 women), age (mean ± SD) 48 ± 15 years, with hyperthyroidism. Serum sclerostin, PTH, calcium, and bone markers [osteocalcin (OC) and collagen type I cross-linked C-telopeptide I (CTX)] were measured at diagnosis of hyperthyroidism and after treatment with thiamazole. Results. After treatment of hyperthyroidism a significant decrease in free T3 (FT3) and free T4 (FT4) concentrations was accompanied by marked decrease of serum sclerostin (from 43.7 ± 29.3 to 28.1 ± 18.4 pmol/L; p<0.001), OC (from 35.6 ± 22.0 to 27.0 ± 14.3 ng/mL; p<0.001), and CTX (from 0.49 ± 0.35 to 0.35 ± 0.23 ng/dL; p<0.005), accompanied by an increase of PTH (from 29.3 ± 14.9 to 39.8 ± 19.8; p<0.001). During hyperthyroidism there was a positive correlation between sclerostin and CTX (rs=0.41, p<0.05) and between OC and thyroid hormones (with FT3  rs=0.42, with FT4  rs=0.45, p<0.05). Conclusions. Successful treatment of hyperthyroidism results in a significant decrease in serum sclerostin and bone markers concentrations, accompanied by an increase of PTH.